Clinical and epidemiological profile of blood donors with positive serology for viral hepatitis in southern Brazil - Silveira,Luciana da (2011)
INTRODUCTION: Positive serological tests for hepatitis viruses B and C at blood banks are an important reason for blood deferral. Additionally, high residual risk for transfusing hepatitis-contaminated blood has been estimated in southern Brazil. This study aimed to identify risk factors for positive serological tests for viral hepatitis (VH) in blood donors (BD). METHODS: A case-control study included consecutive BD with positive serology for VH, between 2008 and 2009. Cases and controls (BD with negative serology for VH) were paired 1:1 by sex and donation date. Assessment of clinical and epidemiological characteristics related to viral hepatitis was conducted. RESULTS: Among 1,282 blood donors (641 cases and 641 controls), those with positive serology for viral hepatitis had higher mean age (p<0.001); higher proportion of replacement donation (p<0.001); first donation (p<0.001); and interviewer deferment (p=0.037), compared to controls. Furthermore, donors with positive tests were less regular donors (p<0.001), had less previous history of rejection (p=0.003) and showed lower hematocrit median before donation (p=0.019). Multivariate analysis demonstrated that age (OR=1.056, 95%CI 1.042-1.069, p<0.001), replacement donation (OR=1.545, 95%CI 1.171-2.038, p=0.002) and first donation (OR=9.931, 95%CI 7.486-13.173, p<0.001) were independently associated with positivity of serological tests for viral hepatitis. CONCLUSIONS: Specific characteristics of blood donors were associated with positive serology for viral hepatitis. These peculiarities should be taken into account when assessing candidates for blood donation.